CHARACTERIZATION OF MORTALITIES REQUIRING AUTOPSY BY A MEDICAL BOARD - Kumar, Anand; Shubhendu, Kumar; Kumar, Sanjay; Mundri, Sawan (Student's Journal of Health Research Africa, 2024)
Background In general, a single autopsy surgeon undertakes medico-legal autopsies; nonetheless, in particular scenarios, a collaboration of medical experts may occur. This study aims to characterize the mortalities necessitating medicolegal autopsies by a Medical Board over an extended timeframe, thereby facilitating the development of a comprehensive profile of such cases pertinent to this region. Methods A cumulative total of 262 records about post-mortem examinations performed by Medical Boards from April 2015 to March 2020 were acquired after the fulfillment of our established criteria through the method of consecutive sampling in this retro-prospective observational study, which was executed within the Department of Forensic Medicine and Toxicology at the Rajendra Institute of Medical Sciences, Ranchi. Results In 17 cases (6.5%), the identification of the deceased individual could not be ascertained. A total of 5.3% (14) of the cases exhibited a considerable degree of decomposition. The majority of the autopsies [19.5% (51)] were conducted on individuals within the 21 to 30 years age demographic, comprising 212 males and 47 females. Nearly half, specifically 46.6% (122), of the autopsies were carried out on individuals identified as adherents of Hinduism, whilst 34.0% (89) were performed on adherents of the Sarna faith. Out of all autopsies, over half, accounting for 55.3% (145), were done on non-tribal people, contrasting with 38.2% (100) that were on tribal people. A significant majority, amounting to 74.0% (194), of the autopsies were conducted on individuals who were married. Conclusion The majority of the autopsies were conducted within the younger demographic strata, exhibiting a significant predominance of male subjects alongside a remarkable scarcity of unidentified and decomposed remains. Recommendations Comprehensive protocols are essential to guarantee that the performance of autopsies by Medical Boards upholds the trust and dependence of legal entities.